Influence of Surgical Techniques on Endoscopic Dacryocystorhinostomy: A Systematic Review and Meta-analysis. (July 2021) - Vinciguerra, Alessandro; Nonis, Alessandro; Resti, Antonio Giordano; Barbieri, Diego; Bussi, Mario; Trimarchi, Matteo
Objective: Endoscopic endonasal dacryocystorhinostomy (END-DCR) has increased as a valid alternative to the classic external approach to treat distal lacrimal obstruction. Different surgical varieties of the END-DCR approach have been proposed with no clear understanding of the best surgical technique. Data Source: A comprehensive research was performed in PubMed, Embase, SCOPUS, and Cochrane databases with a final search on March 2020. Review Methods: The aim of this search was to identify relevant END-DCR procedures performed with mechanical (Mecn-END-DCR) and powered (Pow-END-DCR) approaches to compare their functional success rate. In addition, the influence of mucosal flaps was evaluated. Articles were selected only if they were published later than 2000 and had at least 50 single-clinician surgical procedures performed. Excluded articles included acute infections, cancers, mixed cohort study, and revision cases. Results: A total of 11, 445 publications were identified and 2741 reviewed after screening; 15 articles were included after full-text review (0.6% of the initial articles reviewed). The mean success rate was 91.34% (95% CI, 87.1%-94.3%) for Pow-END-DCR and 89.5% (95% CI, 86.5%-91.9%) for Mecn-END-DCR with no significant difference between the surgical approaches ( P = .43). For mucosal flaps performed during END-DCR, the mean success rate was 89% (95% CI, 86%-91%) if mucosal flaps were used and 92% (95% CI, 88%-95%) if they were not used, with no statistical difference present ( P = .14). Conclusions: Our analyses suggest that there are no differences in outcomes between mechanical and powered approaches in END-DCR and that mucosal flap preservation is not essential to achieve a superior END-DCR outcome.